No fans - No pressure: Referees in professional football during the COVID-19 pandemic - Leitner, M. C.; Richlan, F. (Frontiers in Sports and Active Living, 2021)
Due to the COVID-19 pandemic, European elite football (soccer) leagues played the remaining season 2019/20 without or strongly limited attendance of supporters (i.e., "ghost games"). From a sport psychological perspective this situation poses a unique opportunity to investigate the crowd`s influence on referee decisions and the associated effect of "home advantage". A total of 1286 matches - played in the top leagues of Spain, England, Germany, Italy, Russia, Turkey, Austria and the Czech Republic - were analyzed for results, fouls, bookings and reasons for bookings and contrasted between respective matchdays of season 2018/19 (regular attendance) and season 2019/20 (ghost games). There are two main findings. First, home teams were booked significantly more often with yellow cards for committing fouls in ghost games. Most importantly, this effect was independent of the course of the games. In contrast, bookings for other reasons (criticism and unfair sportsmanship) changed similarly for both home and away teams in ghost games. Second, the overall home advantage effect in the respective elite leagues - identified in the respective matches of the regular 2018/19 season - vanished in the ghost games of the 2019/20 season. Consequently, home teams lost significantly more matches, whereas away teams won significantly more matches. We conclude that the lack of supporters in top European football during the COVID-19 pandemic led to decreased social pressure from the ranks on referees, which also had a potential impact on the home advantage. This implication is consistent both with previous field research in smaller size and experiments in artificial settings. As a result of decreased social pressure, referees assessed the play of home teams more objectively, leading to increased yellow cards awarded for fouls committed by the home teams. Since there were no significant changes in referee decisions against the away teams, we argue that our observations reflect a reduction of unconscious favoritism of referees for the home teams. This key finding also provides a firm empirical basis for the development of novel methods - such as virtual reality interventions - for training referees and thus minimizing the effects of decisions made under social pressure.